Analisis Posisi dan Upaya Peningkatan Indeks Daya Saing Daerah Pada Aspek Pilar Pendidikan Di Kabupaten Konawe Selatan - Ilyas, Ilyas (Jurnal Pendidikan Ekonomi (JUPE), 2021)
This study aims to determine the position and efforts to increase the Regional Competitiveness Index on the education pillar in Konawe Selatan Regency. This study uses a quantitative approach. The data used are primary data and secondary data. Primary data was obtained through a questionnaire, while secondary data in the form of HDI data, education level of the workforce was obtained through documentation/publication studies from the Statistics Agency (BPS) and the Education Office of South Konawe Regency. The data analysis technique used is descriptive analysis. The results showed that the Regional Competitiveness Index of South Konawe Regency was in a high position with a score of 2.66. Efforts made to improve the competitive position of the South Konawe Regency include increasing the average number of years of schooling; the role of local governments that are proactive in taking a persuasive approach to parents of students; providing scholarships for underprivileged students; as well as opening easier access for students to obtain educational services.